Implicaç\~oes do contingenciamento de despesas do Ministério da Saúde para o financiamento federal do sistema Único de Saúde - Fabiola Sulpino Vieira; Sérgio F. Piola (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– The Unified Health System (SUS) financing is a recurrent theme in the sectoral debate. After 28 years since the Federal Constitution promulgation, its failure remains identified as a major structural problem for the public healthcare system consolidation. In the federal government, the spending constraint, the high amount of unpaid commitments and the systematic process of transforming the minimum level resources allocation on actions and public health services (ASPS) into maximum level were factors that contributed to the restriction of the public health financing. In this paper, we analyze the possible implications of government spending constraints, through budget and financial programming, to the SUS federal financing. The following issues relating to expenses on ASPS are discussed: i) limitation of the commitments; ii) limiting of the expenses payment; iii) expenses registration as unpaid commitments; iv) unpaid commitments cancellation; and v) the effect of unpaid commitments on the minimum level of spending on ASPS. Finally, some considerations about the spending constraint to the SUS federal financing are discussed.
Keywords: H510; H610; 330; public health; government expenditures; federal budget